Yield protection as a risk management strategy - Aizikovitz, Jacob (Kansas State University, 2018)
Risk management is critical in crop production as the challenges farmers face on a year to year basis are quite variable due to Mother Nature. There are many tools a farmer can utilize to help manage risk such as crop insurance and forward contracting or hedging. In recent years with lower prices, these tools have been more heavily used than they were a few years ago when corn and soybean prices were $8 and $15 per bushel, respectively. Margins in crop production are tight when market prices are low and input prices are high relative to market prices, and due to land cost. In order for farmers to produce greater profit, they must find ways to lower expenses or produce more bushels to increase their revenue. As margins tighten, farmers typically try to lower expenses to be more profitable rather than trying to increase bushels that would ultimately increase their revenue. When farmers try to reduce expenses, agricultural retailers experience lower revenues holding all else equal; distributors have lower revenues because the retailer is not selling as much, and the manufacturers experience lower revenues because the retailer and distributor are not moving the inventory compared to when farmer margins are larger. This thesis examines how yield protection for grain corn can be utilized as a risk management tool for crop production farmers. This thesis explores how increasing bushels and ultimately increasing revenue by protecting the bushels the crop is physically able to produce, can help manage producer risk. This thesis uses yield protection as a tool alongside crop insurance and marketing, rather than as a tool to replace crop insurance or marketing. Data used for yield protection is replicated fungicide, fungicide with an adjuvant, and fungicide with insecticide, that were evaluated against the untreated check over multiple locations and years across the Midwestern United States. Fungicide data were chosen because it is truly the definition of yield protection, protecting the crop against disease. Fungicides are usually the first products cut from a farmer’s crop production program to help reduce expenses and maintain profitability as margins tighten. The results found in this study are consistent with work conducted at Iowa State University. Results exhibited an increase in corn yield, but were not consistently statistical significant across treatments and location. In conclusion, the average yield increase was not enough over multiple years to pay for itself, and it lacked sufficient evidence. Yield protection does not fit a risk management strategy annually. However, yield protection should be utilized when specific thresholds on disease or insects are present to warrant this strategy.
Keywords: Risk management; Margins; Yield protection